Modern Economy - Hojimurodova Shaxnoza Dilmurod qizi (Zien Journals, 2023)
This article provides information about the role of modern economic theory in the course of human life today, its development, i.e., its role in the life of society.
Keywords: Modern economic views; economy; economic relations; economic activity